PENEMPATAN PEGAWAI DI SEKRETARIAT DAERAH KABUPATEN NATUNA - Prayuda E.01108146, Riky (PublikA, Jurnal Ilmu Administrasi Negara, 2014)
This thesis is intended to provide an understanding of the implementation of staffing in Natuna District Secretariat . Issues regarding staffing in the Secretariat Natuna Regency is quite interesting to study in view of the staffing is not in accordance with the terms of office , especially on employee education specialization . Such circumstances will influence the employee in carrying out its duties and responsibilities , because the positions are not carried in accordance with previously adopted educational specialization . From the study it can be concluded that the implementation of staffing is not referring to education , so there are some positions that do not correspond to formal education , such as the Head of Economics at the handshake by a Bachelor of Engineering majoring in Electrical is ideally more appropriate handshake by an undergraduate Economics Accounting jurisan , while Head of Public Relations chaired by an Economics degree is supposed to be more precise is the Bachelor of Social Science majoring in Communications . Head of Economic supposed to be held by Head of Public Relations for appropriate educational qualifications now . In addition to education , which is a consideration in the placement of employees in an office is previous work experience . It is not too much of a consideration in the deployment of staff in the Secretariat Natuna Regency , because staffing is done on the basis of the presumption of propriety to be placed and can carry out their duties . Knowledge work has a positive and significant influence on employee performance . The more knowledgeable employees in the work the better the performance of employees . And work skills is a must-have in supporting the performance of employees . Skill is one supporting factor in the conduct of an employee 's performance in carrying out its duties and functions in positions carried .. Through writing this essay is also intended , so that the implementation of staffing at the Regional Secretariat is referring to the principle of employment . Implementation of staffing in accordance with the principles of staffing is appropriate to the education , training and leadership training , rank / group , and experience . If that principle is not met then there is another consideration that is based on a decision taken by the Regent .Keywords :Â Personnel Placement, Employment Principles and Conditions Title.Â